2003
DOI: 10.1038/sj.onc.1207179
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Peutz–Jeghers syndrome kinase LKB1 requires its binding to the molecular chaperones Hsp90/Cdc37

Abstract: Peutz-Jeghers syndrome (PJS) is an autosomal dominant disorder characterized by the presence of multiple gastrointestinal polyps and an increased risk for various types of cancers. Inactivating germline mutations of the LKB1 gene, which encodes a serine/threonine kinase, are responsible for the majority of PJS cases. Here, we show that the heteromeric complex containing the molecular chaperones Hsp90 and Cdc37/p50 interacts with the kinase domain of LKB1. Treatment of cells with either geldanamycin or novobioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 53 publications
(55 reference statements)
2
51
0
Order By: Relevance
“…In LKB1 wild-type cells, STRAD␣ is degraded through the proteasome in an Hsp90-dependent manner but turnover is enhanced when LKB1 is mutant. This pathway is similar to the LKB1 degradation pathway where LKB1 interacts with the molecular chaperones Hsp90 and Cdc37/p50 to regulate LKB1 stability and proteasomal degradation (42,43). Based upon our data, we propose a model that when LKB1 is present, STRAD␣ is degraded via the proteasome in an Hsp90-dependent manner but when LKB1 is mutant or absent, the rate of STRAD␣ degradation through this pathway is increased.…”
Section: Pak1mentioning
confidence: 56%
“…In LKB1 wild-type cells, STRAD␣ is degraded through the proteasome in an Hsp90-dependent manner but turnover is enhanced when LKB1 is mutant. This pathway is similar to the LKB1 degradation pathway where LKB1 interacts with the molecular chaperones Hsp90 and Cdc37/p50 to regulate LKB1 stability and proteasomal degradation (42,43). Based upon our data, we propose a model that when LKB1 is present, STRAD␣ is degraded via the proteasome in an Hsp90-dependent manner but when LKB1 is mutant or absent, the rate of STRAD␣ degradation through this pathway is increased.…”
Section: Pak1mentioning
confidence: 56%
“…Protein Analyses and Immunoprecipitation-Cells were lysed 48 h post-transfection, and Western blot analyses and immunoprecipitations were performed as described earlier (14,23) (see supplemental "Materials and Methods"). Quantitative Western blot analyses were performed using Li-Cor Odissey (Li-Cor Biosciences) according to the manufacturer's instruction (see supplemental "Materials and Methods").…”
Section: Methodsmentioning
confidence: 99%
“…The chaperone Hsp90 interacts with and stabilizes LKB1 (Nony et al, 2003;Boudeau et al, 2003a). We and others have shown that cell treatment with geldanamycin (GA), an Hsp90-specific inhibitor, induces the proteasomemediated degradation of LKB1.…”
Section: Lkb1 Stability Is Regulated By the Molecular Chaperone Cdc37mentioning
confidence: 99%
“…We and others have shown that cell treatment with geldanamycin (GA), an Hsp90-specific inhibitor, induces the proteasomemediated degradation of LKB1. It was also reported that the co-chaperone adaptator Cdc37 binds to LKB1 (Nony et al, 2003;Boudeau et al, 2003a). However, whether this interaction is involved in the control of LKB1 protein stability was not determined.…”
Section: Lkb1 Stability Is Regulated By the Molecular Chaperone Cdc37mentioning
confidence: 99%
See 1 more Smart Citation